Titanium dioxide composite material as well as preparation method and application thereof

By configured titanium dioxide precursor solids as a binder, the titanium dioxide composite material that does not contain organic adhesives is prepared, which solves the problem of easily loss and active sites covered by the optical catalyst during the solid load. Sex, suitable for industrial production.

CN119368156APending Publication Date: 2025-01-28YUNNAN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411533800.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing photocatalysts are easily lost during solid loading, and organic binders will cause the occlusion of the active sites of the catalyst, making it difficult to achieve efficient regeneration and reuse.

Method used

The titanium dioxide front -drive solution is used as a binder. Through the combination and thermal treatment with the base, the titanium dioxide composite material that does not contain organic adhesives is prepared, which simplifies the effect of solid load and reduces the effect of the catalyst effect.

Benefits of technology

The efficient and stability of titanium dioxide composite materials is achieved, and the cover of catalysts is avoided by organic adhesives, simplifying the preparation process and reducing costs, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368156A_ABST
    Figure CN119368156A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photocatalysis, and particularly relates to a titanium dioxide composite material as well as a preparation method and application thereof. According to the invention, the prepared titanium dioxide precursor sol is used as a binder to immobilize titanium dioxide, the finally obtained composite material only contains two components of the substrate and the titanium dioxide photocatalyst, and no organic binder exists in the preparation process, so that the influence of the organic binder on covering of the catalyst is avoided; and the influence of the immobilization process on the effect of the catalyst is reduced. The preparation method provided by the invention is simple and easy to implement, low in cost and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalysis, and in particular relates to a titanium dioxide composite material and a preparation method and application thereof. Background Art

[0002] Global resource shortages and ecological environmental degradation have become huge challenges that mankind has to face. Therefore, many new technologies that conform to the concept of sustainable development have developed rapidly. Photocatalysis is such a technology that can use solar energy to solve many resource and environmental problems. However, there are still many obstacles to the large-scale practical application of photocatalysis technology. The low quantum efficiency, poor stability and high manufacturing cost of the photocatalyst itself make its large-scale application difficult. In addition, engineering application research is even more of a shortcoming in the development of photocatalysis technology. A large number of photocatalytic reactions are still in small-scale laboratory research. The catalyst is usually a powder material suspended in a liquid phase system for light irradiation. The reuse of the catalyst is difficult to achieve, which is far from large-scale practical application.

[0003] Nano-TiO2 has good photocatalytic activity, can fully or partially degrade pollutants in the environment, and is non-toxic, resistant to light corrosion, and has good chemical stability, thus receiving much attention and attention from scientific researchers. However, the nano-TiO2 powder suspension system currently used is difficult to precipitate and difficult to recycle due to the fine catalyst particles, resulting in a large loss of active ingredients, which is unfavorable for regeneration and reuse. In order to make photocatalysts easy to recycle, the development of their immobilization technology has become one of the key issues of technological development. Immobilized photocatalysts can relatively easily carry out solid-liquid separation, which can effectively overcome the shortcomings of nano-TiO2 powder that is difficult to recycle and reuse in the wastewater treatment process.

[0004] At present, there are major disadvantages in using organic binders to immobilize TiO2. On the one hand, most photocatalysts have strong oxidizing ability after being excited by light, which can decompose the binder and make the catalyst easily lost. On the other hand, organic binders will largely cover the active sites of the catalyst, causing it to lose its activity.

[0005] The prior art discloses a metal mesh-supported titanium dioxide photocatalyst and its preparation method, which directly configures a titanium dioxide precursor sol as the supported titanium dioxide and a binder. The prior art also discloses a method for supporting titanium dioxide and its application, which utilizes silica sol and a silane coupling agent as the supported binder, avoiding the problem of titanium dioxide decomposing the binder and causing the catalyst to be easily lost. However, the binder will cover the catalyst to a large extent. The prior art also discloses a method for supporting photocatalysts, but the preparation of modified TiO2 is relatively cumbersome, and the modification method may involve the introduction of other elements, which affects the catalyst effect. Summary of the Invention

[0006] The purpose of the present invention is to provide a titanium dioxide composite material and its preparation method and application. The method provided by the present invention does not contain an organic binder, thereby avoiding the influence of the organic binder on the covering of the catalyst and reducing the influence of the immobilization process on the catalyst effect.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a titanium dioxide composite material, comprising the following steps:

[0009] After mixing the titanium source, ethanol and acetylacetone, adding an ethanol aqueous solution to the obtained mixture under stirring, adjusting the pH value of the system to acidic and continuing to stir to obtain a binder;

[0010] After mixing titanium dioxide and a binder, immersing the substrate into the mixture to obtain a substrate with titanium dioxide attached;

[0011] The substrate with titanium dioxide is heat-treated to obtain the titanium dioxide composite material.

[0012] Preferably, the titanium source includes one or more of tetrabutyl titanate, titanium tetraisopropoxide and titanium tetrachloride;

[0013] The volume ratio of the titanium source, ethanol and acetylacetone is 1-4:45-48:1;

[0014] The volume ratio of ethanol to water in the ethanol aqueous solution is 2-4:46-48;

[0015] The stirring time is 10 to 20 minutes.

[0016] Preferably, the mass ratio of titanium dioxide to binder is 1 to 2:100;

[0017] The mixing of titanium dioxide and binder comprises stirring and ultrasonication in sequence;

[0018] The stirring speed is 150-250 rpm and the stirring time is 20-40 min;

[0019] The ultrasonic time is 0.5 to 1.5 hours.

[0020] Preferably, the method for preparing titanium dioxide comprises the following steps:

[0021] The tobacco stem shreds are immersed in an isopropyl alcohol solution containing a titanium source, left to stand in air, and then calcined to obtain the titanium dioxide.

[0022] Preferably, the titanium source in the titanium source-containing isopropanol solution comprises one or more of tetrabutyl titanate, titanium tetraisopropoxide and titanium tetrachloride;

[0023] The mass concentration of the titanium source in the titanium source-containing isopropanol solution is 5 to 15%;

[0024] The immersion time is 24 to 48 hours; the standing time is 24 to 48 hours.

[0025] Preferably, the calcination temperature is 450-550° C., the heating rate to the calcination temperature is 1-2° C. / min, and the calcination time is 5-10 h.

[0026] Preferably, the substrate comprises a glass sheet, a quartz sheet, an ITO conductive glass or a metal sheet;

[0027] The substrate is immersed for 15 to 60 seconds.

[0028] Preferably, the heat treatment temperature is 350-500° C., the heating rate to the heat treatment temperature is 1-5° C. / min, and the holding time is 60-240 min.

[0029] The present invention also provides a titanium dioxide composite material prepared by the preparation method described in the above technical solution, comprising a substrate and titanium dioxide located on the surface of the substrate.

[0030] The present invention also provides the use of the titanium dioxide composite material described in the above technical solution as a photocatalyst.

[0031] The present invention provides a method for preparing a titanium dioxide composite material, comprising the following steps: mixing a titanium source, ethanol, and acetylacetone, adding an ethanol aqueous solution to the obtained mixed solution under stirring, adjusting the pH value of the system to acidic, and continuing to stir to obtain a binder; mixing the titanium dioxide and the binder, immersing a substrate to obtain a substrate with titanium dioxide attached; and heat-treating the substrate with titanium dioxide attached to obtain the titanium dioxide composite material. The present invention uses a configured titanium dioxide precursor sol as a binder to immobilize titanium dioxide, and the composite material finally obtained contains only two components: the substrate and the titanium dioxide photocatalyst. No organic binder is present in the preparation process, thereby avoiding the influence of the organic binder on the covering of the catalyst and reducing the influence of the immobilization process on the catalyst effect. The preparation method provided by the present invention is simple and easy to implement, low in cost, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the SEM image of the titanium dioxide obtained in Example 1;

[0033] Figure 2This is the XRD pattern of titanium dioxide obtained in Example 1. DETAILED DESCRIPTION

[0034] The present invention provides a method for preparing a titanium dioxide composite material, comprising the following steps:

[0035] After mixing the titanium source, ethanol and acetylacetone, adding an ethanol aqueous solution to the obtained mixture under stirring, adjusting the pH value of the system to acidic and continuing to stir to obtain a binder;

[0036] After mixing titanium dioxide and a binder, immersing the substrate into the mixture to obtain a substrate with titanium dioxide attached;

[0037] The substrate with titanium dioxide is heat-treated to obtain the titanium dioxide composite material.

[0038] The method comprises mixing a titanium source, ethanol and acetylacetone, adding an ethanol aqueous solution to the obtained mixed solution under stirring, adjusting the pH value of the system to be acidic, and continuing stirring to obtain a binder.

[0039] In the present invention, the titanium source preferably includes one or more of tetrabutyl titanate, titanium tetraisopropoxide and titanium tetrachloride; the volume ratio of the titanium source, ethanol and acetylacetone is preferably 1-4:45-48:1, specifically 4:45:1, 1:48:1, 3:46:1, 2:47:1; the volume ratio of ethanol and water in the ethanol aqueous solution is preferably 2-4:46-48, specifically 3:47, 4:46, 2:48; the volume ratio of the mixed solution and the ethanol aqueous solution is preferably 1:1; the acidic pH value is preferably 3-5, specifically 3, 4, 5; the stirring speed is preferably 200 rpm; and the continued stirring time is preferably 10-20 min.

[0040] After obtaining the binder, the present invention mixes titanium dioxide and the binder, and then immerses the substrate in the mixture to obtain a substrate with titanium dioxide attached thereto.

[0041] In the present invention, the titanium dioxide is preferably commercially available titanium dioxide or homemade titanium dioxide.

[0042] In the present invention, the method for preparing titanium dioxide preferably comprises the following steps:

[0043] The tobacco stem shreds are immersed in an isopropyl alcohol solution containing a titanium source, left to stand in air, and then calcined to obtain the titanium dioxide.

[0044] Before the impregnation, the present invention further preferably includes washing and drying the tobacco stem shreds; the drying temperature is preferably 70°C.

[0045] In the present invention, the titanium source in the titanium source-containing isopropanol solution preferably includes one or more of tetrabutyl titanate, titanium tetraisopropoxide, and titanium tetrachloride; the mass concentration of the titanium source in the titanium source-containing isopropanol solution is preferably 5-15%, specifically 5%, 10%, or 15%. The present invention does not particularly limit the preparation method of the titanium source-containing isopropanol solution; the titanium source can be directly added to isopropanol and stirred, and the stirring time is preferably 10 minutes.

[0046] In the present invention, the impregnation time is preferably 24 to 48 hours, and the impregnation is preferably carried out under closed conditions. In the present invention, the standing method preferably includes: wrapping the impregnated tobacco stem shreds with plastic wrap, puncturing holes, and then standing in air; the standing time is preferably 24 to 48 hours.

[0047] In the present invention, the calcination temperature is preferably 450°C to 550°C, specifically 450°C, 500°C, or 550°C; the heating rate to the calcination temperature is preferably 1°C to 2°C / min; and the holding time is preferably 5 to 10 hours, specifically 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours. In the present invention, the calcination can remove the tobacco stem template to obtain a titanium dioxide material.

[0048] In the present invention, the mass ratio of the titanium dioxide and the binder is preferably 1 to 2:100; the mixing of the titanium dioxide and the binder preferably includes stirring and ultrasonication in sequence; the stirring speed is preferably 150 to 250 rpm, specifically 150 rpm, 200 rpm or 250 rpm; the time is preferably 20 to 40 min, specifically 20 min, 30 min or 40 min; the ultrasonic time is preferably 0.5 to 1.5 h, specifically 0.5 h, 1.0 h or 1.5 h.

[0049] In the present invention, the substrate preferably comprises a glass sheet, a quartz sheet, an ITO conductive glass, or a metal sheet. In the present invention, the metal sheet preferably comprises a nickel foam, a titanium foam, or a stainless steel foam; the pore size of the metal sheet is preferably 100 μm. Prior to immersing the substrate, the present invention also preferably includes pre-treating the substrate.

[0050] In the present invention, when the substrate is a glass or quartz sheet, the pretreatment preferably includes: sequentially rinsing the substrate with water, cleaning with a detergent, and ultrasonically washing with deionized water; after drying, alkali leaching in a sodium hydroxide solution; ultrasonically washing the substrate in deionized water after the alkali leaching; drying, storing the substrate in an ethanol solution for later use, and drying the substrate at 95°C before use. In the present invention, the alkali leaching time is preferably 24 hours.

[0051] In the present invention, when the substrate is ITO conductive glass, the pretreatment process preferably includes: cleaning the substrate in toluene, acetone and ethanol in sequence, then ultrasonicating the substrate in deionized water, drying the substrate and storing it in an ethanol solution for standby use, and then taking it out and drying it at 95°C before use; the ultrasonication time is preferably 10 to 30 minutes.

[0052] In the present invention, when the substrate is a metal sheet, the pretreatment process preferably includes: placing the substrate in clean water containing a detergent for a first ultrasonic treatment, taking it out and rinsing it with water, placing it in deionized water for a second ultrasonic treatment, and storing it in a cool and dry place after drying; the time for the first ultrasonic treatment is preferably 10 to 30 minutes, and the time for the second ultrasonic treatment is preferably 5 to 30 minutes.

[0053] In the present invention, the substrate is preferably immersed for 15 to 60 seconds, specifically 15 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds, or 60 seconds; the substrate is preferably immersed 1 to 2 times. After the immersion, the present invention also preferably includes air-drying the substrate with the adhesive for 24 hours.

[0054] After obtaining the substrate with titanium dioxide attached, the present invention performs heat treatment on the substrate with titanium dioxide attached to obtain the titanium dioxide composite material.

[0055] In the present invention, the heat treatment temperature is preferably 350-500°C, specifically 350°C, 400°C, 450°C or 500°C; the heating rate to the heat treatment temperature is preferably 1-5°C / min, specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min; the holding time is preferably 60-240min, specifically 60min, 100min, 150min, 180min, 200min or 240min; the heat treatment is preferably carried out in a muffle furnace. In the present invention, after the heat treatment, the obtained material is preferably cooled naturally to room temperature.

[0056] The present invention also provides a titanium dioxide composite material prepared by the preparation method described in the above technical solution, comprising a substrate and titanium dioxide located on the surface of the substrate.

[0057] In the present invention, the solid loading amount of titanium dioxide on the substrate is preferably 2 to 5 mg / cm 2 , specifically 1 mg / cm 2 , 2mg / cm 2 , 3mg / cm 2 , 4mg / cm 2 or 5mg / cm 2 .

[0058] The present invention also provides the use of the titanium dioxide composite material described in the above technical solution as a photocatalyst.

[0059] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0060] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0061] Example 1

[0062] 2.0g of tobacco stems were washed with pure water, dried in a 70°C oven, and immersed in a 10% TBOT isopropanol solution that had been stirred for 10 minutes. The solution was then immersed in a sealed beaker for 24 hours. After filtration, the impregnated tobacco stems were wrapped in plastic wrap and punctured. The leaves were allowed to stand in air for 24 hours before being transferred to a crucible and calcined at 450°C (heating rate of 2°C / min) for 10 hours to remove the tobacco stems and obtain titanium dioxide.

[0063] A quartz plate with a size of 50 mm*50 mm was sequentially rinsed with water, cleaned with a detergent, and ultrasonically washed with deionized water. After drying, it was alkali-soaked in a sodium hydroxide solution for 24 hours. After the alkali soaking, it was ultrasonically washed in deionized water. After drying, it was placed in an ethanol solution for storage. Before use, it was taken out and dried at 95°C to obtain a pretreated substrate.

[0064] Mix tetrabutyl titanate, ethanol, and acetylacetone in a volume ratio of 4:45:1 to obtain 50 mL of Solution A. Mix water and ethanol in a volume ratio of 3:47 to obtain 50 mL of Solution B. Stir Solution A at 200 rpm and slowly add Solution B dropwise. Adjust the pH of the system to 4 and continue stirring for 15 minutes to obtain the binder.

[0065] 1 g of the titanium dioxide obtained above was added to 100 g of the binder, stirred at 200 rpm for 30 min, and then ultrasonically treated for 1 h to obtain an impregnation solution;

[0066] Immerse the pretreated substrate in the immersion solution for 30 seconds, slowly remove it, repeat this process once or twice, and then naturally dry it for 24 hours to obtain a substrate with titanium dioxide attached;

[0067] The substrate with titanium dioxide was placed in a muffle furnace and heated to 400°C at a heating rate of 3°C / min for heat treatment, and the temperature was kept at this temperature for 120 min. After heat treatment, the substrate was naturally cooled to room temperature to obtain a titanium dioxide composite material with a titanium dioxide solid loading of 3 mg / cm 2 .

[0068] Example 2

[0069] An ITO conductive glass sheet with a size of 50 mm*50 mm was cleaned in toluene, acetone and ethanol in sequence, then ultrasonicated in deionized water for 10 min, dried and stored in an ethanol solution, and then taken out and dried at 95°C before use to obtain a pretreated substrate;

[0070] Mix tetrabutyl titanate, ethanol, and acetylacetone in a volume ratio of 1:48:1 to obtain 50 mL of Solution A. Mix water and ethanol in a volume ratio of 2:48 to obtain 50 mL of Solution B. Stir Solution A at 200 rpm and slowly add Solution B dropwise. Adjust the pH of the system to 3 and continue stirring for 15 minutes to obtain the binder.

[0071] 1.5 g of the titanium dioxide obtained in Example 1 was added to 100 g of the binder, stirred at 200 rpm for 30 min, and then ultrasonically treated for 1 h to obtain an impregnation solution;

[0072] Immerse the pretreated substrate in the immersion solution for 30 seconds, slowly remove it, repeat this process once or twice, and then naturally dry it for 24 hours to obtain a substrate with titanium dioxide attached;

[0073] The substrate with titanium dioxide was placed in a muffle furnace and heated to 400°C at a heating rate of 3°C / min for heat treatment. The temperature was kept at this temperature for 120 min. After heat treatment, the substrate was naturally cooled to room temperature to obtain a titanium dioxide composite material with a titanium dioxide solid loading of 2 mg / cm 2 .

[0074] Example 3

[0075] A nickel foam with a size of 50 mm*50 mm and a pore size of 100 μm was placed in clean water containing a detergent and ultrasonically treated for 15 minutes. After being taken out and rinsed with water, it was placed in deionized water and ultrasonically treated for 10 minutes. After drying, it was stored in a cool and dry place to obtain a pretreated substrate.

[0076] Mix tetrabutyl titanate, ethanol, and acetylacetone in a volume ratio of 3:46:1 to obtain 50 mL of Solution A. Mix water and ethanol in a volume ratio of 4:46 to obtain 50 mL of Solution B. Stir Solution A at 200 rpm and slowly add Solution B dropwise. Adjust the pH of the system to 5 and continue stirring for 15 minutes to obtain the binder.

[0077] 2 g of the titanium dioxide obtained in Example 1 was added to 100 g of the binder, stirred at 200 rpm for 30 min, and then ultrasonically treated for 1 h to obtain an impregnation solution;

[0078] Immerse the pretreated substrate in the immersion solution for 30 seconds, slowly remove it, repeat this process once or twice, and then naturally dry it for 24 hours to obtain a substrate with titanium dioxide attached;

[0079] The substrate with titanium dioxide was placed in a muffle furnace and heated to 400°C at a heating rate of 3°C / min for heat treatment, and the temperature was kept at this temperature for 120 min. After heat treatment, the substrate was naturally cooled to room temperature to obtain a titanium dioxide composite material with a titanium dioxide solid loading of 3 mg / cm 2 .

[0080] Example 4

[0081] A titanium foam with a size of 50 mm*50 mm and a pore size of 100 μm was placed in clean water containing a detergent and ultrasonically treated for 15 minutes. After being taken out and rinsed with water, it was placed in deionized water and ultrasonically treated for 5 minutes. After drying, it was stored in a cool and dry place to obtain a pretreated substrate.

[0082] Mix tetrabutyl titanate, ethanol, and acetylacetone in a volume ratio of 2:47:1 to obtain 50 mL of Solution A. Mix water and ethanol in a volume ratio of 3:47 to obtain 50 mL of Solution B. Stir Solution A at 200 rpm and slowly add Solution B dropwise. Adjust the pH of the system to 4 and continue stirring for 15 minutes to obtain the binder.

[0083] 1.5 g of the titanium dioxide obtained in Example 1 was added to 100 g of the binder, stirred at 200 rpm for 30 min, and then ultrasonically treated for 1 h to obtain an impregnation solution;

[0084] Immerse the pretreated substrate in the immersion solution for 30 seconds, slowly remove it, repeat this process once or twice, and then naturally dry it for 24 hours to obtain a substrate with titanium dioxide attached;

[0085] The substrate with titanium dioxide was placed in a muffle furnace and heated to 400°C at a heating rate of 3°C / min for heat treatment. The temperature was kept at this temperature for 120 min. After heat treatment, the substrate was naturally cooled to room temperature to obtain a titanium dioxide composite material with a titanium dioxide solid loading of 2 mg / cm 2 .

[0086] Example 5

[0087] A foamed stainless steel sheet with a size of 50 mm*50 mm and a pore size of 100 μm was placed in clean water containing a detergent and ultrasonically treated for 15 minutes. After being taken out and rinsed with water, it was placed in deionized water and ultrasonically treated for 5 minutes. After drying, it was stored in a cool and dry place to obtain a pretreated substrate.

[0088] Mix tetrabutyl titanate, ethanol, and acetylacetone in a volume ratio of 1:48:1 to obtain 50 mL of Solution A. Mix water and ethanol in a volume ratio of 3:47 to obtain 50 mL of Solution B. Stir Solution A at 200 rpm and slowly add Solution B dropwise. Adjust the pH of the system to 4 and continue stirring for 15 minutes to obtain the binder.

[0089] 1.5 g of the titanium dioxide obtained in Example 1 was added to 100 g of the binder, stirred at 200 rpm for 30 min, and then ultrasonically treated for 1 h to obtain an impregnation solution;

[0090] Immerse the pretreated substrate in the immersion solution for 30 seconds, slowly remove it, repeat this process once or twice, and then naturally dry it for 24 hours to obtain a substrate with titanium dioxide attached;

[0091] The substrate with titanium dioxide was placed in a muffle furnace and heated to 400°C at a heating rate of 3°C / min for heat treatment. The temperature was kept at this temperature for 120 min. After heat treatment, the substrate was naturally cooled to room temperature to obtain a titanium dioxide composite material with a titanium dioxide solid loading of 2 mg / cm 2 .

[0092] Performance Testing

[0093] Test Example 1

[0094] Figure 1 The SEM image of the titanium dioxide obtained in Example 1 is Figure 1 It can be seen that the obtained titanium dioxide has the unique microscopic morphology of biomass materials of tobacco stems and is composed of tiny crystal particles;

[0095] Figure 2 The XRD pattern of titanium dioxide obtained in Example 1 is as follows. Figure 2 It can be seen that the obtained titanium dioxide material is anatase crystal form.

[0096] Test Example 2

[0097] The titanium dioxide composite materials obtained in Examples 1-5 were encapsulated in a quartz photoreactor with an internal volume of 50 mm x 50 mm x 5 mm, equipped with a water inlet and outlet, to test pollutant degradation performance. Using a quartz plate without catalyst as a blank control, the system was tested at various flow rates under irradiation with a 300W xenon lamp. After the system stabilized, water was collected from the outlet for analysis. The results are shown in Table 1.

[0098] Table 1 Removal rate of methylene blue (25 ppm) by titanium dioxide composite materials at different flow rates

[0099]

[0100] As can be seen from Table 1, the titanium dioxide obtained in Examples 1 to 5 all have a good degradation effect on methylene blue (25 ppm). The degradation rate can reach a maximum of 97% when the flow rate is as low as 5 mL / h, and the degradation rate is as low as 84% ​​when the flow rate is as high as 20 mL / h.

[0101] Although the above embodiment provides a detailed description of the present invention, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a titanium dioxide composite material, characterized in that: The following steps are involved: After mixing the titanium source, ethanol and acetylacetone, adding an ethanol aqueous solution to the obtained mixed solution under stirring, adjusting the pH value of the system to acidic and continuing to stir to obtain a binder; After mixing titanium dioxide and a binder, immersing a substrate into the mixture to obtain a substrate with titanium dioxide attached; The substrate with titanium dioxide attached thereto is subjected to heat treatment to obtain the titanium dioxide composite material.

2. The preparation method according to claim 1, characterized in that: The titanium source includes one or more of tetrabutyl titanate, titanium tetraisopropoxide and titanium tetrachloride; The volume ratio of the titanium source, ethanol and acetylacetone is 1-4:45-48:1; The volume ratio of ethanol to water in the ethanol aqueous solution is 2-4:46-48; The stirring time is 10 to 20 minutes.

3. The preparation method according to claim 1, characterized in that: The mass ratio of titanium dioxide to binder is 1 to 2:100; The mixing of titanium dioxide and a binder comprises stirring and ultrasonicating in sequence; The stirring speed is 150-250 rpm and the time is 20-40 min; The ultrasonic time is 0.5 to 1.5 hours.

4. The preparation method according to claim 1, characterized in that: The preparation method of titanium dioxide comprises the following steps: The tobacco stem shreds are immersed in an isopropanol solution containing a titanium source, left to stand in the air, and then calcined to obtain the titanium dioxide.

5. The preparation method according to claim 4, characterized in that: The titanium source in the titanium source isopropanol solution includes one or more of tetrabutyl titanate, titanium tetraisopropoxide and titanium tetrachloride; The mass concentration of the titanium source in the titanium source-containing isopropanol solution is 5 to 15%; The immersion time is 24 to 48 hours; the standing time is 24 to 48 hours.

6. The preparation method according to claim 4, characterized in that: The calcination temperature is 450-550° C., the heating rate to the calcination temperature is 1-2° C. / min, and the calcination time is 5-10 hours.

7. The preparation method according to claim 1, characterized in that: The substrate includes a glass sheet, a quartz sheet, an ITO conductive glass or a metal sheet; The substrate is immersed for 15 to 60 seconds.

8. The preparation method according to claim 1, characterized in that: The heat treatment temperature is 350-500° C., the heating rate to the heat treatment temperature is 1-5° C. / min, and the heat preservation time is 60-240 min.

9. The titanium dioxide composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The invention comprises a substrate and titanium dioxide located on the surface of the substrate.

10. Use of the titanium dioxide composite material according to claim 9 as a photocatalyst.

Citation Information

Patent Citations

  • Method for preparing composite photocatalyst containing activated carbon coating

    CN101757902A

  • Method for preparing and loading nanometer titanium dioxide sol

    CN108439465A

  • TiO2 composite hydrophobic icephobic coating and preparation method thereof

    CN109535782A

  • Preparation method and application of cobalt titanate-titanium dioxide composite catalyst electrode

    CN110790348A

  • Method for preparing TiO2 photocatalytic material by taking tobacco stem shreds as template and application of TiO2 photocatalytic material

    CN113304739A